Shifting from Individualism to Genericism: Personalization as a Conspiracy Theory - Mohseni Ahooei, Ebrahim (Žurnalistikos tyrimai, 2023)
With severe mistrust around classical approaches to consciousness, this paper claims that arguments around the notion of “personalization” of media or messages are grounded on a misinterpretation. Based on the two presuppositions of respective differentiation of human beings and the power to make choices based on reasoning, these approaches have been the reference for many well-known scientific studies, mainly in the fields of media studies, economics, political sciences, and psychology. Despite refuting their results via meta-analyses, such theories have so far sought to maintain their position by resorting to conspiracy theories, the promotion of which, ironically, leads to the syndrome of skepticism, which supports its origins in a vicious circle. While these approaches have been ubiquitous in so-called cognitive priming, projection of mass movements and political abuses of the concepts such as misinformation or disinformation, the mainstream workouts in the fields including but not limited to Perception Management, Artificial Intelligence, and Machine Learning have significantly relied on both de-individualistic and irrational processes. This article aims to prove that the ontological claims about the centrality of individualism in the latest fields of all media and communication technological procedures are grounded in a conspiracy theory. Relying on the method of epistemological reasoning, this article attempts to prove that individualism and personalization in the field of the media industry are the principal tools of social control through the spread of skepticism, which takes advantage of the fictitious nature of the new media sphere for commercial and political purposes.